Envisioning role of ammonia oxidizing bacteria in bioenergy production and its challenges: a review. (18th August 2022) - Chawley, Parmita; Rana, Anu; Jagadevan, Sheeja
Abstract: Ammonia oxidizing bacteria (AOB) play a key role in the biological oxidation of ammonia to nitrite and mark their significance in the biogeochemical nitrogen cycle. There has been significant development in harnessing the ammonia oxidizing potential of AOB in the past few decades. However, very little is known about the potential applications of AOB in the bioenergy sector. As alternate sources of energy represent a thrust area for environmental sustainability, the role of AOB in bioenergy production becomes a significant area of exploration. This review highlights the role of AOB in bioenergy production and emphasizes the understanding of the genetic make-up and key cellular biochemical reactions occurring in AOB, thereby leading to the exploration of its various functional aspects. Recent outcomes in novel ammonia/nitrite oxidation steps occurring in a model AOB – Nitrosomonas europaea propel us to explore several areas of environmental implementation. Here we present the significant role of AOB in microbial fuel cells (MFC) where Nitrosomonas sp. play both anodic and cathodic functions in the generation of bioelectricity. This review also presents the potential role of AOB in curbing fuel demand by producing alternative liquid fuel such as methanol and biodiesel. Herein, the multiple roles of AOB in bioenergy production namely: bioelectricity generation, bio-methanol, and biodiesel production have been presented. Graphical Abstract: UF0001